Utilization Of Digital Media As A Learning Strategy In The Campus Environment - Norhayatun Norhayatun; Desyara Misli Ananda; Mif Takhul Jannah; Mayanda Rahmawati; Karina Azizah Maharani (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The advancement of digital technology has significantly influenced higher education, particularly in the use of digital media as a learning strategy. This study analyzes the effectiveness, challenges, and implementation strategies of digital media through a qualitative approach involving literature review and case studies in several universities. The results indicate that digital media enhances student engagement, supports collaborative learning, and provides access to diverse learning resources. Challenges identified include gaps in digital literacy, limited infrastructure, and the need for pedagogical adjustments. The integration of digital media requires careful planning, continuous support, and alignment with educational objectives to maximize its learning potential.